Changes in Consumption Patterns of Makassar People and Their Implications for Social Welfare in South Sulawesi - Edi Ferdinant (Generasi Sains Indonesia, 2024)
This study examines the changing consumption styles among the Makassar humans in South Sulawesi, focusing at the socio-economic factors influencing these shifts and their implications for social welfare. Using a quantitative research technique and statistical analyses including regression, ANCOVA, and Pearson correlation, the examine investigates the relationship among profits, age, and spending on intake styles. The findings display substantial changes in consumption behaviors, particularly inspired by means of earnings levels, technological improvements, and cultural factors. The consequences spotlight a strong fine correlation between earnings and spending, emphasizing the function of economic factors in shaping client decisions. These findings make a contribution to a better understanding of consumer conduct dynamics in Makassar and offer insights for policymakers, companies, and network leaders in selling inclusive economic boom and social properly-being.